I am attempting to translate the following Haskell code to Javascript:
fix_poly :: [[a] -> a] -> [a]
fix_poly fl = fix (\self -> map ($ self) fl)
where fix f = f (fix f)
I have trouble understanding ($ self)
though. Here is what I've achieved so far:
const structure = type => cons => {
const f = (f, args) => ({
["run" + type]: f,
[Symbol.toStringTag]: type,
[Symbol("args")]: args
});
return cons(f);
};
const Defer = structure("Defer") (Defer => thunk => Defer(thunk));
const defFix = f => f(Defer(() => defFix(f)));
const defFixPoly = (...fs) =>
defFix(self => fs.map(f => f(Defer(() => self))));
const pair = defFixPoly(
f => n => n === 0
? true
: f.runDefer() [1] (n - 1),
f => n => n === 0
? false
: f.runDefer() [0] (n - 1));
pair[0] (2); // true expected but error is thrown
The error is Uncaught TypeError: f.runDefer(...)[1] is not a function
.
Here is the source.
The definition of defFixPoly
has an extra layer of Defer
than it should. Since self
is already a Defer
value, you can just pass it directly to f
rather than wrapping it again.
const defFixPoly = (...fs) =>
defFix(self => fs.map(f => f(self)));
const structure = type => cons => {
const f = (f, args) => ({
["run" + type]: f,
[Symbol.toStringTag]: type,
[Symbol("args")]: args
});
return cons(f);
};
const Defer = structure("Defer") (Defer => thunk => Defer(thunk));
const defFix = f => f(Defer(() => defFix(f)));
const defFixPoly = (...fs) =>
defFix(self => fs.map(f => f(self)));
const pair = defFixPoly(
f => n => n === 0
? true
: f.runDefer() [1] (n - 1),
f => n => n === 0
? false
: f.runDefer() [0] (n - 1));
console.log(pair[0] (2)); // true expected
This now defines mutually recursive isEven
and isOdd
functions.
const isEven = pair[0];
const isOdd = pair[1];